2023
DOI: 10.2337/ds22-0056
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses’ Comfort With Diabetes Management and Technology From 2012 to 2019

Abstract: OBJECTIVE School nurses are integral to optimizing diabetes management for students with type 1 diabetes. The aim of this study was to describe the use of diabetes technology in schools over time and assess school nurses’ comfort level performing diabetes management tasks. STUDY DESIGN From 2012 to 2019, school nurses who attended a diabetes education program completed a survey about their experience and comfort level with di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Comprehensive programs have shown improvement in quality of life, improved health literacy and increased engagement in school activities for youth with diabetes [ 40 ]. However, school nurses report challenges with chronic care management including inadequate time and resources, challenges related to communication with families [ 41 ▪ , 42 ▪▪ ], lack of experience and comfort with chronic care, low rates of comfort with diabetes technologies [ 43 ▪ ], and misconceptions about diabetes all of which can result in inadequate or suboptimal care [ 38 ]. To combat these challenges, studies have demonstrated that continuing education, computer-based trainings, and provision of resource libraries effective in improving comfort and self-assessed competence in managing diabetes for school nurses and staff [ 38 ].…”
Section: Application Of School-based Health To Obesity and Type 2 Dia...mentioning
confidence: 99%
“…Comprehensive programs have shown improvement in quality of life, improved health literacy and increased engagement in school activities for youth with diabetes [ 40 ]. However, school nurses report challenges with chronic care management including inadequate time and resources, challenges related to communication with families [ 41 ▪ , 42 ▪▪ ], lack of experience and comfort with chronic care, low rates of comfort with diabetes technologies [ 43 ▪ ], and misconceptions about diabetes all of which can result in inadequate or suboptimal care [ 38 ]. To combat these challenges, studies have demonstrated that continuing education, computer-based trainings, and provision of resource libraries effective in improving comfort and self-assessed competence in managing diabetes for school nurses and staff [ 38 ].…”
Section: Application Of School-based Health To Obesity and Type 2 Dia...mentioning
confidence: 99%